Adalimumab induced mononeuritis multiplex in a patient with refractory rheumatoid arthritis: a case report - Makol, Ashima (BioMed Central, 2008)
BACKGROUND: Anti tumor necrosis factor agents are a valuable addition to the armamentarium against rheumatoid arthritis but have some serious side effects which clinicians should be aware about. CASE PRESENTATION: We present a case of a 54 year old Caucasian male with refractory rheumatoid arthritis who developed mononeuritis multiplex four weeks after starting adalimumab therapy. CONCLUSION: Complete resolution of neurological and electromyography findings was seen upon stopping therapy. These agents can be a double-edged sword in the management of rheumatological illnesses. Though they help treat refractory disease, their potential side effects can include mononeuritis multiplex which can be recognized by means of clinical features, electromyography and nerve biopsy as depicted in our case.